1883-1884 Va. Acts 180, ch. 143, § 1 - (:unkn) unknown (My University, 1884)
Prohibited the concealed carry of any pistol, dirk, bowie-knife, razor, slung-shot, or any weapon of the like kind. Violators fined not less than twenty but no more than one hundred dollars. Violators also punished with confiscation of the weapon.
Keywords: CARRY - CONCEALED